Catalytic hydrolysis of cellulose to glucose: On the influence of graphene oxide morphology under microwave radiation. Issue 2 (April 2023) - Frecha, E.; Torres, D.; Remón, J.; Gammons, R.; Matharu, A.S.; Suelves, I.; Pinilla, J.L.
Abstract: Carbon nanostructures provide a unique platform for the synthesis of novel catalysts for biomass conversion. In this work, a set of graphene oxide (GO)-based materials (nanofibers (GONF), sheets of few-layers (FLGO), and quantum dots (GOQD)), differing structurally in morphology and size, was prepared from fishbone-carbon nanofibers (CNF) and their catalytic behavior was compared on the hydrolysis of amorphous cellulose under microwave (MW) radiation. First, the influence of the reaction temperature (135–180 ºC), holding time (0–120 min), catalyst morphology and cellulose/water ratio (0.25–2.0 wt%) was thoroughly screened and compared with conventional heating mode. The use of GO morphologies in concert with MW energy showed the potential to achieve similar kinetic profiles than previously reported sulfonated carbons (110 kJ/mol) but using considerably less amount of catalyst (cellulose-to-catalyst ratio 12-fold lower). Overall, the reactivity of the GO-catalyst was related to their degree of oxidation/exfoliation, decreasing as follows: GOQD > FLGO > GONF. Compared with conventional heating, MW-technology enabled higher loadings of cellulose (2.0 vs. 0.25 wt%) to be processed in a shorter time (20 min instead of 24 h), which is a landmark achievement toward process intensification. Graphical Abstract: ga1 Highlights: Microwave-assisted hydrolysis of amorphous cellulose catalyzed by graphene oxide. The hydrolytic ability was correlated with the oxidation/exfoliation degree of GO. The influence of process variables was set and compared with conventional heating.